Development of Interactive Multimedia on Ablution and Prayer Learning to Introduce Religious and Moral Values for Kindergarten (Journal of Primary Education, 2019)
The purpose of this research is to develop interactive multimedia learning to introduce religious and moral values (prayer and ablution) for kindergarten. Multimedia forms in compact disk (CD) format. This research method is research and development. The subjects of this research were 47 students of kindergarten. The results of the research have been developed by Interactive Multimedia Learning in kindergarten students with good categories according to expert validation and suitable for learning. Based on t-test obtained tvalue is smaller than ttable = 0.05 which shows that the implementation of Interactive Learning Ablution and Prayer Multimedia can significantly introduce religious and moral values. By implementing CDs on learning students can get to know the stage of ablution and prayer and practice them. In practice there are still difficulties experienced by student. In ablution activities that is when washing feet and prayer activities while sitting between two prostrations.